Pengaruh Sales Growth dan Capital Intensity Terhadap Financial Distress, Dimoderasi Operating Capacity (Lembaga Pengembangan Kinerja Dosen, 2025)
The property and real estate sector is a vital component of the Indonesian economy, yet it faces financial challenges due to its high dependency on external financing. This study investigates the impact of sales growth and capital intensity on financial distress, and the moderating role of operating capacity. Using a quantitative approach and purposive sampling, the research collected 80 data observations from 16 property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The data was analyzed using Moderated Regression Analysis (MRA). The results indicate that sales growth has no effect on financial distress, while capital intensity has a significant influence. Although operating capacity cannot individually moderate these relationships, it can collectively moderate the effect of both independent variables on financial distress. The study concludes that capital intensity is a key factor for company management in this sector to consider in mitigating the risk of financial hardship.